Unveiling seasonal changes in trophic structure of fishery community in the offshore waters of southern Zhejiang Province of China: Insights from stable isotope analysis - Xiujin Wei; Chunxia Gao; Yiwen Liu; Siquan Tian; Richard Kindong; Yin Wang (Ecological Indicators, 2024)
Understanding an ecosystem’s trophic structure is essential for determining the dynamic interplay between natural and human-induced changes. However, limited knowledge of local food web structures, especially the seasonal trophic structure, hinders our understanding of ecosystem’ stability and dynamics. The offshore waters of southern Zhejiang Province of China are amongst the important fishing waters in China, which are undergoing multiple stressors, such as over-exploitation, global warming, and acidification. This study investigated the seasonal changes in the trophic structure and trophic spectrum of fishery community in this region based on δ13C–δ15N isotope metrics and identified the key types of organisms determining the stability of food webs in different seasons. The results showed that the trophic structure in summer significantly diverged from those of other seasons, with benthivorous fish predominating, higher trophic positions, and feeding specialization of predators. The lowest trophic level and length of the trophic spectrum were observed in spring and were is attribute to the generally smaller size of the species in the community. The winter community showed maximal resource occupancy but the lowest trophic redundancy due to specialized top predators, suggesting higher vulnerability to disturbance. Based on the bi-plot of δ13C–δ15N isotope values, it can be found that Planktivorous and benthivorous fish occupy a key position in the food web structure. Seasonal fluctuations in the trophic structure of fishery community illustrated the diversity and complexity of food webs, and our study provided insights for characterizing marine ecological processes, which were conducive to the restoration of offshore fisheries and the development of management strategies.